Exploring the Implementation of Differentiated Instruction in Vocational English Classrooms - Cindy Rizky Kamsurya; Karolis Anaktototy; Rosina Lekawael (ITScience (Information Technology and Science), 2026)
This study aims to explore the challenges an English teacher faces in implementing differentiated instruction in a vocational English classroom. The study was conducted at a Muhammadiyah vocational high school in Ambon, Indonesia, using a qualitative single-case study design, as described by Yin (2014). The participant in this study was an English teacher with experience teaching in a vocational context. Data were collected through classroom observation, semi-structured interviews, and document analysis. The data were analysed using thematic analysis to identify patterns related to the challenges the teacher encountered. The findings reveal that the teacher experienced several significant challenges in implementing differentiated instruction. These include a lack of professional training, limited theoretical understanding of differentiated instruction, and difficulty in conducting initial assessments of students’ readiness, interests, and learning profiles. In addition, the teacher faced challenges in differentiating instruction, particularly in grouping students and providing varied student products. The study also found that traditional teaching habits and mindset contributed to the difficulty in adopting differentiated practices. Overall, the findings suggest that while there is an awareness of differentiated instruction, its implementation remains limited and not fully aligned with its theoretical principles. This study highlights the importance of providing professional development and practical support to help teachers effectively implement differentiated instruction in vocational English classrooms.